The ESAT-6 Protein of Mycobacterium tuberculosis Interacts with Beta-2-Microglobulin (β2M) Affecting Antigen Presentation Function of Macrophage - Sreejit, Gopalkrishna (Public Library of Science, 2014)
ESAT-6, an abundantly secreted protein of Mycobacterium tuberculosis (M. tuberculosis) is an important virulence factor, inactivation of which leads to reduced virulence of M. tuberculosis. ESAT-6 alone, or in complex with its chaperone CFP-10 (ESAT-6:CFP-10), is known to modulate host immune responses; however, the detailed mechanisms are not well understood. The structure of ESAT-6 or ESAT-6:CFP-10 complex does not suggest presence of enzymatic or DNA-binding activities. Therefore, we hypothesized that the crucial role played by ESAT-6 in the virulence of mycobacteria could be due to its interaction with some host cellular factors. Using a yeast two-hybrid screening, we identified that ESAT-6 interacts with the host protein beta-2-microglobulin (β2M), which was further confirmed by other assays, like GST pull down, co-immunoprecipitation and surface plasmon resonance. The C-terminal six amino acid residues (90–95) of ESAT-6 were found to be essential for this interaction. ESAT-6, in complex with CFP-10, also interacts with β2M. We found that ESAT-6/ESAT-6:CFP-10 can enter into the endoplasmic reticulum where it sequesters β2M to inhibit cell surface expression of MHC-I-β2M complexes, resulting in downregulation of class I-mediated antigen presentation. Interestingly, the ESAT-6:β2M complex could be detected in pleural biopsies of individuals suffering from pleural tuberculosis. Our data highlight a novel mechanism by which M. tuberculosis may undermine the host adaptive immune responses to establish a successful infection. Identification of such novel interactions may help us in designing small molecule inhibitors as well as effective vaccine design against tuberculosis.